2020
DOI: 10.21203/rs.3.rs-76172/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The outcomes of Ilizarov treatment in aseptic nonunions of the tibia stratified by treatment strategies and surgical techniques

Abstract: INTRODUCTIONNonunions of the tibia, particularly those located in the distal third of the bone, are relatively common in clinical practice. There is no gold standard for the treatment of nonunions of the tibia. The purpose of our study was to assess the results of treatment with the Ilizarov method in patients with aseptic nonunions of the tibia, depending on the employed treatment strategies and surgical techniques.MATERIALS AND METHODSA total of 75patients with Ilizarov treatment of aseptic nonunions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It has been reported that the average number of complications per patient range from 0.67 to 2.27. 15 The average number of complications reported by Aktuglu et al 32 was just 0.29 and the reoperation rate was 12.5%. The authors attribute this to the carefully chosen and meticulous follow-up of each patient.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been reported that the average number of complications per patient range from 0.67 to 2.27. 15 The average number of complications reported by Aktuglu et al 32 was just 0.29 and the reoperation rate was 12.5%. The authors attribute this to the carefully chosen and meticulous follow-up of each patient.…”
Section: Discussionmentioning
confidence: 92%
“…Currently, there are multiple approaches to repair segmental tibia defects including autogenous or allogeneic bone graft, [4][5][6] nonvascular bula graft, 7,8 vascularized bular or iliac crest bone ap transplantation, [9][10][11][12][13][14] Ilizarov bone transport, [15][16][17][18][19] masquelet technique, [20][21][22][23] and so forth. All of them presented good e cacy in repairing tibial defects.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, fractured bone can self-repair and regenerate via intramembranous and endochondral ossification, in which bone tissue is woven and precursor cells differentiate into osteoblasts in a callus 6 . However, in approximately 10% of fractures, union is delayed or unsuccessful due to unstable fixation, blood supply interruptions, or, in most cases, the presence of infection [7][8][9] . There is an urgent medical need to develop new strategies to promote bone healing and prevent delayed union or nonunion.…”
Section: Introductionmentioning
confidence: 99%